OP0021 Effects of tnf-alpha, il-1 beta and il-15 on the production/expression of opg and rankl by synovial fluid mononuclear cells and fibroblast-like synoviocytes isolated from patients with rheumatoid arthritis (ra). (1st June 2001) - Zió³kowska, M; Kurowska, MS; Radzikowska, A; £uszczykiewicz, G; Dziewczopolski, W; Kowalczewski, J; Maslinski, W
Abstract : Background: The receptor activator of nuclear factor κB (RANKL), its receptor RANK and osteoprotegerin (OPG) are key regulators of bone remodelling that influence immune functions as well. RANKL is responsible for the development and activation of osteoclasts. OPG, a soluble decoy receptor for RANKL, competes with RANK for RANKL binding. Proinflammatory cytokines (TNF-α, IL-1b and IL-15) play critical role in the pathogenesis of RA and bone erosions. Objectives: To compare the effects of TNF-α, IL-1b and IL-15 on the production/expression of OPG and RANKL by synovial fluids mononuclear cells (SFMC) and fibroblast-like synoviocytes (FLS) isolated from RA patients. Methods: SFMC and FLS were obtained from 8 RA patients. The isolated SFMC and FLS (cultured in vitro for 2–5 passages) were stimulated with recombinant human TNF-α, IL-1b or/and IL-15. The concentrations of OPG in culture supernatants were measured by a specific ELISA and the expression of surface RANKL and OPG was tested using flow cytometry. Results: SFMC and FLS from RA patients spontaneously produced considerable levels of OPG. The production of OPG by FLS was strongly enhanced by TNF-α and IL-1b, but not by IL-15. In contrast, the production of OPG by SFMC was only slightly enhanced in the presence of TNF-α, IL-1b or IL-15. Interestingly, additive effects of IL-15 and IL-1b or IL-15 and TNF-α on OPG production by SFMC were observed. In addition to the soluble form, high levels of surface expressed OPG on CD33 + /SFMC, but not on CD3 + /SFMC, was observed. The high expression of RANKL was found on CD33 + /SFMC, intermediate on CD3 + /SFMC and low on FLS. Tested cytokines modulate the expression of RANKL and OPG, in a complex, cell type and time dependent manner. Conclusion: TNF-α, IL-1b and IL-15 affecting balance between RANKL and OPG influence inflammation and bone destruction in RA patients.